Coagonist of GLP-1 and glucagon decreases liver inflammation and atherosclerosis in dyslipidemic condition. (25th February 2018) - Patel, Vishal; Joharapurkar, Amit; Kshirsagar, Samadhan; Sutariya, Brijesh; Patel, Maulik; Pandey, Dheerendra; Patel, Hiren; Ranvir, Ramchandra; Kadam, Shekhar; Patel, Dipam; Bahekar, Rajesh; Jain, Mukul
Abstract: Dyslipidemia enhances progression of atherosclerosis. Coagonist of GLP-1 and glucagon are under clinical investigation for the treatment of obesity and diabetes. Earlier, we have observed that coagonist reduced circulating and hepatic lipids, independent of its anorexic effects. Here, we investigated the role of coagonist of GLP-1 and glucagon receptors in complications of diet-induced dyslipidemia in hamsters and humanized double transgenic mice. Hamsters fed on high fat high cholesterol diet were treated for 8 weeks with coagonist of GLP-1 and glucagon receptors (75 and 150 μg/kg). Pair-fed control was maintained. Cholesterol fed transgenic mice overexpressing hApoB100 and hCETP with coagonist (300 μg/kg) for 4 weeks. After the completion of treatment, biochemical estimations were done. Coagonist treatment reduced triglycerides in plasma, liver and aorta, plasma cholesterol and hepatic triglyceride secretion rate. Expressions of HMG-CoA reductase and SBREBP-1C were reduced and expressions of LDLR, CYP7A1, ABCA1 and ABCB11 were increased in liver, due to coagonist treatment. Coagonist treatment increased bile flow rate and biliary cholesterol excretion. IL-6 and TNF-α were reduced in plasma and expression of TNF-α, MCP-1, MMP-9 and TIMP-1 decreased in liver. Treatment with coagonist reduced oxidative stress in liver and aorta. Energy expenditure was increased and respiratory quotient was reduced by coagonist treatment. These changes were correlated with reduced hepatic inflammation and lipids in liver and aorta in coagonist treated hamsters. Coagonist treatment also reduced lipids in cholesterol-fed transgenic mice. These changes were independent of glycaemia and anorexia observed after coagonist treatment. Long term treatment with coagonist of GLP-1 and glucagon receptor ameliorated diet-induced dyslipidemia and atherosclerosis by regulating bile homeostasis, liver inflammation and energy expenditure. Highlights: GLP-1/glucagon coagonism reduces hyperlipidemia in transgenic mice and hamsters. HMG-CoA reductase and SBREBP-1C were reduced by GLP-1/glucagon coagonism. GLP-1/glucagon coagonism regulates bile homeostasis via ABCA1, ABCB11, and CYP7A1 . GLP-1/glucagon coagonism reduces TNF-α, MCP-1, MMP-9 and TIMP-1 in liver. GLP-1/glucagon coagonism reduces progression of atherosclerosis and inflammation.